Adsorption and Desorption Characteristics of Simiao Yong’an Decoction on Macroporous Adsorption Resins - Wei Jiao; Erhu Liu; Yao Luo; Yanxin Niu; Yongxue Guo (Separations)
In this study, to identify an appropriate macroporous resin for the purification of the crude extract derived from Simiao Yong’an Decoction (SMYAD), five distinct resins were evaluated based on their adsorption and desorption performance. Through this comparative analysis, D101 macroporous adsorption resin was determined to be the most suitable candidate. Investigations into the adsorption mechanism revealed that the process followed pseudo-second-order kinetics and was well described by the Langmuir isotherm model. Thermodynamic analysis further indicated the spontaneous and exothermic nature of the adsorption process. Through systematic optimization, the ideal purification parameters for SMYAD were established as follows: sample loading volume—6 bed volumes (BV), eluent concentration—90% ethanol (v/v), and eluent volume—3 BV, with both adsorption and desorption flow rates maintained at 3 BV/h. Finally, the purification effect was evaluated by fingerprint and similarity analysis. Under the optimal purification process, the content of the five index components was as follows: harpagide (4.26 mg/g), chlorogenic acid (38.37 mg/g), ferulic acid (4.78 mg/g), liquiritin (7.42 mg/g), and harpagoside (10.25 mg/g). The yield of the five components ranged from 70.74% to 86.26%. In conclusion, this approach demonstrates rapid processing capabilities and high efficiency, offering valuable methodological insights for the isolation and purification of complex traditional Chinese medicine formulations using macroporous adsorption resins.